Factors associated with the duration of telephone observation and consultation sessions provided by the Hiroshima Prefecture Follow-up Center in the later stages of the COVID-19 pandemic in Japan - Yui Yumiya; Mikikazu Itakura; Noriyuki Shiroma; Hanako Murayama; Chiaki Taguchi; Toki Yamashita; Chiaki Tokubo; Takahito Yoshida; Tatsuhiro Nagata; Odgerel Chimed-Ochir; Ami Fukunaga; Kanako Kitahara; et al. (PLoS ONE, 2026)
Background Identifying the factors that affected the workload of Public Health Centers (PHCs) during the recent COVID-19 pandemic may help such institutions improve their preparedness and response to future pandemics and public health crises. Therefore, this study aimed to examine factors related to the duration of telephone observation and consultation sessions administered by nurses at the Hiroshima Prefecture Follow-Up Center to patients with COVID-19 recuperating at home during the pandemic. Methods This cross-sectional study used data from 22,490 telephone observation and consultation sessions collected using the COVID-19 Japan-Surveillance in Post-Extreme Emergencies and Disasters form by nurses at the Hiroshima Prefecture Follow-Up Center (Japan) from 1 November 2022 to7 May 2023. Long call duration was defined as ≥ 15 minutes. Study days were classified into low-, middle-, and high-incidence groups using the 25th and 75th percentiles of the 7-day moving average of newly diagnosed COVID-19 cases. Multivariable logistic regression models were fitted separately for each incidence group. Results Across the low-, middle-, and high-incidence groups, age ≥ 80 years, two or more symptoms, medical consultation on physical symptoms, and consultation about family members or close contacts were consistently associated with long telephone observation and consultation sessions. In the middle- and high-incidence groups, long telephone sessions were significantly more common at nighttime and among patients who requested physician involvement, and less common among pregnant women, whereas longer evening sessions were observed only in the high-incidence group. Conclusions In the later stages of the COVID-19 pandemic, several factors found to be associated with long telephone observation and consultation sessions depended on the number of newly diagnosed cases. These results may help PHCs and Follow-Up Centers plan staffing, triage, and workflows when personnel and time are limited.